1983
DOI: 10.1007/bf00392984
|View full text |Cite
|
Sign up to set email alerts
|

Coaction of light and cytokinin in photomorphogenesis

Abstract: Intact mustard seedlings were treated with zeatin and photomorphogenetically active light in different ways: (1) hormone treatment preceding light treatment, (2) light treatment preceding hormone treatment, (3) hormone and light applied simultaneously. Under all experimental conditions the effect of the hormone treatment is multiplicative to the light effect with regard to the increase of cotyledon area. However, the hormone effect is additive to the light effect with regard to increases of the level of NADPH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Further, applications of a CK ( 6 N‐BA) have no significant effect on elongation of our sunflower hypocotyls under either R/FR ratio. Tong, Kasemir & Mohr (1983) have also reported that for intact mustard seedlings, application of CKs did not affect light quality‐mediated growth increases.…”
Section: Discussionmentioning
confidence: 90%
“…Further, applications of a CK ( 6 N‐BA) have no significant effect on elongation of our sunflower hypocotyls under either R/FR ratio. Tong, Kasemir & Mohr (1983) have also reported that for intact mustard seedlings, application of CKs did not affect light quality‐mediated growth increases.…”
Section: Discussionmentioning
confidence: 90%
“…whether the signaling pathways are independent and whether the responses are additive or multiplicative (Kasemir and Mohr, 1982;Tong et al, 1983). The relationship between light and cytokinin may differ for other developmental responses, including other de-etiolation responses.…”
Section: Discussionmentioning
confidence: 99%
“…Whether Pfr and BA affectphy mRNA abundance via the same or distinct signal transduction pathways remains to be determined. Other investigators [ 11,38] report that Pfr and cytokinins act independently. Flores and Tobin [13,14] observed that Pfr and BA both increase cab mRNA levels.…”
Section: Discussionmentioning
confidence: 99%